Effects of Nevadensin from Rice Paddy Herb (Limnophila aromatica) on Growth and Physiological Parameters of Hybrid Catfish (Clarias macrocephalus × C. gariepinus) - Jankham, Aroon; Rattana, Khwanduean; Sangchanjiradet, Supavee; Dasri, Kajohnpong; Matchima, Kajita; Munglue, Phukphon (Journal of Food Health and Bioenvironmental Science, 2023)
This study examined the effects of dietary supplementation of nevadensin, a flavonoid isolated from rice paddy herb (Limnophila aromatica), on growth and physiological parameters of hybrid catfish (Clarias macrocephalus × C. gariepinus). Fish (initial weight of 5.00 ± 1.00 g) were fed with the diets containing 0 (control), 10, 30, and 50 mg nevadensin/kg feed for 8 weeks. Growth parameters, feed intake, and feed efficiency were significantly improved (P<0.05) by the diets containing 30 and 50 mg nevadensin. Survival rate and organosomatic indices for the intestine, gill, heart, kidney, and spleen were not significantly different (P>0.05) among the groups. However, the hepatosomatic index in fish fed with 30 mg nevadensin/kg diet was significantly increased (P<0.05) when compared with the control. A significant improvement (P<0.05) in villi heights, muscular thicknesses, goblet cells, and microvilli heights was detected in fish fed with nevadensin containing diets. Villi widths, total enterocyte heights and supranucleus heights decreased significantly (P<0.05) in fish fed with nevadensin supplemented diets. Red blood cells and white blood cells in fish fed with supplemented diets were significantly higher (P<0.05) than those in fish fed with the control diet. Hemoglobin and hematocrit significantly increased (P<0.05) in fish fed with 50 mg nevadensin/kg diet compared to the control. The highest level of lymphocyte was observed in fish fed with 10 mg nevadensin. Blood biochemical values were not significantly different (P>0.05) in any of the treated groups compared to the control. In conclusion, the results indicate that nevadensin could be used as a natural feed additive to improve somatic growth and physiological parameters of hybrid catfish. By using the secondorder polynomial regression analysis, the optimal concentration of nevadensin for cultured catfish was estimated to be between 30.64 and 31.14 mg/kg diet.